Formal Email Writing Convention: Differences Between Native and Non-native Students - Shahid, Shama E (Journal of NELTA, 2020)
The use of emails in student-faculty communication is a regulated process. The regulations are formulated in order to ensure that the correspondences are in line with the institutional requirements and maintain professionalism. There is limited information about such regulations amongst native students and non-native students regarding formal email writing conventions.This study examines the formal email writing conventions of non-native students under a regulated environment. A purposive non-probability sampling of 10 non-native students from a British university was collected. The findings indicated that language prowess, request letter acts, and the use of formality had positive impacts on formal email writing among non-native students. It can be concluded from the above findings that teachers of ESL should pay attention to how students formulate the structure and content of emails as these matters directly impact their writing capability.